PENGARUH KOMPOS SERBUK SABUT KELAPA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT PADA TANAH PODSOLIK MERAH KUNING - Ishak Dianisius; Agustina Listiawati; Inpurwanto Inpurwanto (Fakultas Pertanian Universitas Tanjungpura, 2022)
This study aims to determine the effect of composted coconut coir dust on growth and yield of cayenne pepper on red yellow podzolic soil. This research was conducted in the experimental farm of the Faculty of Agriculture, University of Tanjungpura Pontianak, started from February to July 2014. This study used a field experiment with completely randomized design consisting of single factor i.e composted coconut coir dust, with six level treatments: S1 (800 g/polybag); S2 (900 g/polybag); S3 (1000 g/polybag); S4 (1100 g/polybag); S5 (1200 g/polybag); dan S6 (1300 g/polybag), consists of 4 replications, with 3 plant samples each. The variables observed in this study include, plant height (cm), number of fruit per plant (fruits), the fruit biomass per plant (g), total dry biomass (g), and root volume (ml). The results showed that the application of composted coconut coir dust here not a significanlly affected plant height, number of fruit per plant, the fruit biomass, total plant dry biomass, and root volume.